KAJIAN IMPLEMENTASI PRINSIP-PRINSIP KONSTRUKSI RAMPING MENGGUNAKAN BUILDING INFORMATION MODELING DI INDUSTRI KONSTRUKSI - Fenni Nabila (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2021)
As a major problem in construction, schedule delays and cost overruns have been caught the attention of the government in supporting domestic development. In improving the quality of construction in Indonesia, the government plans to set higher standards on construction by using new principles and technologies such as lean construction and Building Information Modeling (BIM). Lean and BIM are two innovations that have been present for a long time, but their advantages are often carried out in a manner separate. This research dedicated to answering the advantages, challenges, and interactions from both innovations in the construction industry. The research method was a literature review then analyzing with bibliometric analysis and meta-analysis. Based on the results of 20 studies had found that the main benefit of both innovations namely reducing the duration of construction and increasing visualization, meanwhile, the main obstacle is the accuracy required in the construction design. Interaction of the two produce communication efficiencies that maximize collaboration between collaborators.